KEBEBASAN BERAGAMA, RELIGIUSITAS DAN PEMBANGUNAN EKONOMI - Edi Purwanto (Manna Rafflesia, 2023)
This study employs a literature review methodology to investigate the interplay among religious freedom, religiosity, and economic development. It examines how religious freedom influences religiosity levels and economic growth, drawing on various research propositions and empirical evidence. The research relies on reputable international journal sources and keywords related to religious economy, competition, markets, and their impact on religiosity and economic development. The study reveals a significant relationship between religious freedom and religiosity, highlighting seven key propositions, including the role of state involvement in regulating religious activities, the effects of unregulated religious activities, and the impact on societal acceptance of religious symbols and rituals. It also explores the connection between religious freedom and economic development, emphasizing that it is integral to civil and political liberties, removing barriers to innovation, trade, and investment and ultimately contributing to social stability and cultural diversity. In conclusion, this study illuminates the complex connections between religious freedom, religiosity, and economic development, offering insights for policymakers to protect religious rights, encourage pluralism, and foster a diverse and inclusive society that values religious freedom and economic growth.